The Concept of Evaluative Language in Malay Newspaper Discourse - Sarikon, Suhaini; Abdullah, Roksana Bibi (Talenta Publisher, 2024)
This article delves into the exploration of Evaluative Language Theory within the discourse of Malay newspapers. The study draws upon two primary news sources: